CLINICOPATHOLOGICALCHARACTERISTICS OF NASOPHARYNGEALCARCINOMA AT CENTRAL GENERAL HOSPITAL PROF. DR. I.G.N.G. NGOERAH DENPASAR IN 2021-2022 - Heriani, Ni Komang; Paskarani, Putu Erika; Winarti, Ni Wayan (E-Jurnal Medika Udayana, 2024)
ABSTRACT Nasopharyngeal carcinoma (NPC) epidemiologically occupies the fourth position as the highest number of malignancy cases in Bali, Indonesia. The most common histological type of NPC cases are non-keratinizing squamous cell carcinoma (NKSCC) undifferentiated subtype. This research aims to know the clinicopathological aspect of nasopharyngeal carcinoma at Central General Hospital Prof. Dr. I.G.N.G Ngoerah Denpasar in 2021-2022 regarding the distribution of age range, gender, education, occupation, clinical stage, histological type, as well as the results of anamnesis. The research design is a descriptive study of 70 cases of NPC at Central General Hospital Prof. Dr. I.G.N.G Ngoerah Denpasar from 2021 to 2022. Samples were collected retrospectively from secondary data using a total sampling technique through a cross-sectional study, samples were obtained from medical record data and hospital management system of Central General Hospital Prof. Dr. I.G.N.G Ngoerah Denpasar. In this study, the most cases of NPC were found in the range of 51-60 years old (32.9%), male sex (65.7%), high school education status (48.6%), private employee employment (32.9%), anamnesis results of a lump in the neck (77.1%), stage IVA (40%), and with the histological type of NKSCC undifferentiated subtype (90%). Men have twice the risk of suffering from NPC compared to women, most cases have complained of a lump in the neck and other symptoms such as nasal congestion, tinnitus, headaches. The most common histological type found is the NKSCC undifferentiated subtype, which mostly occurs in advanced stages of an IVA. Keywords : Clinicopathology, NPC, Nasopharynx